COMPARISON OF MISOPROSTOL WITH OXYTOCIN IN THIRD STAGE OF LABOUR - Subedi, Nilam; Sharma, Deepanjali; Das, Rubby (Journal of Universal College of Medical Sciences, 2018)
Introduction: Postpartum Haemorrhage (PPH) is one of the leading causes of maternal mortality worldwide. A simple measure to prevent PPH is active management of third stage of labour (AMTSL). This prospective study was conducted in Universal College of Medical Sciences and Teaching Hospital, Tribhuvan University, Bhairahawa where misoprostol 600 mcg orally was compared with the standard oxytocin regime in active management of third stage of labour. Materials and Methods: A total of 100 women were selected to receive either 600 mcg misoprostol orally or 10 IU oxytocin intramuscularly. The incidences of postpartum hemorrhage and side effects were examined. Results: Both groups were comparable in age, parity, gestational age, pre-delivery hemoglobin, and duration of labor. There was no significant differences between the misoprostol and oxytocin groups in terms of blood loss 96% vs 100% had blood loss of < 500 ml, p=0.475). And incidence of PPH (4% vs 0%). None of the group had severe PPH i.e. blood loss> 1000 ml. The duration of the third stage of labor, a secondary outcome measure was shorter in the misoprostol group than in the oxytocin group (7.02±2.26 SD vs 8.44±4.08 SD, p=0.034). Two women of oxytocin group received a blood transfusion. The adverse effects of shivering and pyrexia were encountered more frequently in the misoprostol than in the oxytocin group (2% vs 38%, p<0.001, P<0.001; and 2% vs 10%, p=0.207). No major surgical intervention for atonic PPH was needed and no maternal deaths occurred in either group. Conclusion: Misoprostol 600 mcg orally is equally as effective as standard oxytocin regime in AMTSL to prevent PPH and can be safely used in the peripheral institutions or by midwives where there is lack of trained personnel and storage facility. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 19-21